2018
DOI: 10.1001/jamacardio.2018.3945
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race/Ethnicity With Oral Anticoagulant Use in Patients With Atrial Fibrillation

Abstract: IMPORTANCE Black and Hispanic patients are less likely than white patients to use oral anticoagulants for atrial fibrillation. Little is known about racial/ethnic differences in use of direct-acting oral anticoagulants (DOACs) for atrial fibrillation. OBJECTIVE To assess racial/ethnic differences in the use of oral anticoagulants, particularly DOACs, in patients with atrial fibrillation. DESIGN, SETTING, AND PARTICIPANTS This cohort study used data from the Outcomes Registry for Better Informed Treatment of At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 46 publications
8
105
0
Order By: Relevance
“…46,49 A 2018 study comparing the rates of prescription of OACs among Black, White, and Hispanic AF patients calculated a 27% decrease in the likelihood of receiving NOACs in Black patients but deemed that figure insignificant after accounting for socioeconomic factors. 56 A recent 2020 study, however, found that Black, Asian, and other minority ethnics were in fact, significantly less likely to receive any OACs, the difference continuing to be significant even after accounting for socioeconomic factors. 57 The efficacy and required doses of OACs have not been performed in populations with adequate representation of ethnic minorities, and therefore cannot be commented on at this time.…”
Section: Arrhythmiasmentioning
confidence: 95%
See 1 more Smart Citation
“…46,49 A 2018 study comparing the rates of prescription of OACs among Black, White, and Hispanic AF patients calculated a 27% decrease in the likelihood of receiving NOACs in Black patients but deemed that figure insignificant after accounting for socioeconomic factors. 56 A recent 2020 study, however, found that Black, Asian, and other minority ethnics were in fact, significantly less likely to receive any OACs, the difference continuing to be significant even after accounting for socioeconomic factors. 57 The efficacy and required doses of OACs have not been performed in populations with adequate representation of ethnic minorities, and therefore cannot be commented on at this time.…”
Section: Arrhythmiasmentioning
confidence: 95%
“…Inconsistent results have been yielded from the various studies that have been performed evaluating the reduced prescription of non–vitamin K oral anticoagulants (NOACs) in minority ethnics 46,49 . A 2018 study comparing the rates of prescription of OACs among Black, White, and Hispanic AF patients calculated a 27% decrease in the likelihood of receiving NOACs in Black patients but deemed that figure insignificant after accounting for socioeconomic factors 56 . A recent 2020 study, however, found that Black, Asian, and other minority ethnics were in fact, significantly less likely to receive any OACs, the difference continuing to be significant even after accounting for socioeconomic factors 57 .…”
Section: Disparities In Treatmentsmentioning
confidence: 99%
“… 24 Historically, there has been decreased adoption of novel therapies among Black patients as well as among female patients and those with low socioeconomic status. 25 , 26 , 27 The objective of this study was to evaluate trends in SGLT2 inhibitor prescription by race/ethnicity, gender, and socioeconomic status between 2015 (the year of publication of EMPA-REG) and 2019. We also assessed the association of race/ethnicity, gender, and socioeconomic status with SGLT2 inhibitor use among commercially insured patients with type 2 diabetes in the US, including those with heart failure with reduced ejection fraction (HFrEF), CKD, and atherosclerotic cardiovascular disease (ASCVD); individuals with these comorbidities were evaluated because of the demonstrated benefit of SGLT2 inhibitor use in these particular subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…11 There is decreased adoption of advanced cardiovascular therapeutics among Black, Latinx, and low-income patients. 12 , 13 , 14 , 15 Demographic studies have shown that patients with AF who underwent catheter ablation were mostly White and male. 16 Racial and sex inequities in receipt of certain AF-related therapies were demonstrated among Medicare patients.…”
Section: Introductionmentioning
confidence: 99%